2018
DOI: 10.1177/1541204018757038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Childhood Polyvictimization on Victimization in Juvenile Correctional Facilities: The Mediating Role of Trauma Symptomatology

Abstract: Polyvictimization refers to multiple forms of victimization experienced by youths. The extent to which aggregated or cumulative early life victimization increases risk of victimization within juvenile correctional facilities is unclear. Furthermore, pathways from early polyvictimization to facility victimization may be partly explained by trauma symptomatology. Drawing upon the extant polyvictimization literature, this study explores both composite and cumulative effects of childhood victimization on later vic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 77 publications
0
26
0
2
Order By: Relevance
“…For example, Yeater, Montanaro, and Bryan () found that 66.7 percent of justice‐involved girls reported experiencing sexual revictimization over the course of two years. Further, in data drawn from a nationally representative sample of incarcerated youth, Yoder, Hodge, Ruch, and Dillard () found that trauma symptomatology mediated the association between past victimization and physical and sexual revictimization of youth while in detention. Importantly, studies have confirmed that sexually abused youth are at increased risk for engaging in unsafe sex, substance misuse, and attachments to abusive partners, all of which increase the danger of revictimization (Bramsen et al, ; Gidycz et al, ; Orcutt, Erickson, & Wolfe, ), and that this is especially true for girls and young women.…”
Section: Prevailing Theories Of Posttraumatic Self‐destructive and Rimentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Yeater, Montanaro, and Bryan () found that 66.7 percent of justice‐involved girls reported experiencing sexual revictimization over the course of two years. Further, in data drawn from a nationally representative sample of incarcerated youth, Yoder, Hodge, Ruch, and Dillard () found that trauma symptomatology mediated the association between past victimization and physical and sexual revictimization of youth while in detention. Importantly, studies have confirmed that sexually abused youth are at increased risk for engaging in unsafe sex, substance misuse, and attachments to abusive partners, all of which increase the danger of revictimization (Bramsen et al, ; Gidycz et al, ; Orcutt, Erickson, & Wolfe, ), and that this is especially true for girls and young women.…”
Section: Prevailing Theories Of Posttraumatic Self‐destructive and Rimentioning
confidence: 99%
“…For traumatized adolescents, running away from home has been identified as a risky behavior associated particularly with the threat of revictimization (Haynie et al, ; Kim, Tajima, Herrenkohl, & Huang, ), particularly among traumatized girls in the justice system (Kerig & Schindler, ). Girls who flee abusive home lives by running away are vulnerable to a host of dangers on the streets, including commercial sexual exploitation and cooptation into participation in “survival crimes” that increase the risk not only for exposure to harm (Chesney‐Lind, Morash, & Stevens, ) but to juvenile arrest and incarceration in facilities where exposure to further victimization is prevalent (Dierkhising, Lane, & Natsuaki, ; Mendel, ; Yoder et al, ).…”
Section: Alternative Models Of the Functions Underlying Posttraumaticmentioning
confidence: 99%
“…The results from this study suggest the need to confront the structures that foster violence through social domains, including associations with parents/caregivers, deviant peers, and their influence on PTSD symptoms. Specifically, other scholars have documented trauma and victimization within juvenile correctional facilities as an area of vital interest (Ford et al, 2013; Hodge & Yoder, 2017; Kerig, 2018; Yoder et al, 2019). Consequently, the trauma-offending link requires early and effective responses to trauma/victimization to halt future juvenile justice involvement (Yoder et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other research study findings, some girls sought out these peers for protection during a fight or other illegal activity (Jones, 2009). This further indicates a direct relationship between victimization (abuse/trauma) and offending among this population (McGee & Foriest, 2009;Yoder et al, 2019). Consequently, girls with trauma histories are more likely than their counterparts without such violent exposures to socialize with antisocial peer groups (Adams & East, 1999), thereby further exacerbating dangerous behaviors leading to trauma exposures and PTSD symptoms.…”
Section: Negative Peer Norms and Ptsdmentioning
confidence: 99%
See 1 more Smart Citation